Differential kinetics of human cytomegalovirus load and antibody responses in primary infection of the immunocompetent and immunocompromised host - Gerna, Giuseppe; Lilleri, Daniele; Fornara, Chiara; Bruno, Francesca; Gabanti, Elisa; Cane, Ilaria; Furione, Milena; Revello, M. Grazia (Journal of general virology, 2015)
The comparative long-term kinetics of human cytomegalovirus (HCMV) load and HCMV-specific antibody responses in the immunocompetent and immunocompromised solid-organ transplanted host during primary HCMV infection was investigated. In total, 40 immunocompetent subjects and 17 transplanted patients were examined for viral load as well as for IgG antibody responses to HCMV glycoproteins gH/gL/pUL128L, gH/gL and gB, and neutralizing antibodies in ARPE-19 epithelial cells and human fibroblasts. In parallel, the CD4(+) and CD8(+) HCMV-specific T-cell responses were determined by cytokine flow cytometry. Transplanted patients reached significantly higher viral DNA peaks, which persisted longer than in immunocompetent subjects. The ELISA-IgG responses to the pentamer, gH/gL and gB were significantly higher in primary infections of the immunocompetent until six months after onset, with the two antibody levels then overlapping from six to 12 months. Antibody levels neutralizing infection of epithelial cells were significantly higher in transplanted patients after six months, persisting for up to a year after transplantation. This trend was not observed for antibodies neutralizing infection of human fibroblasts, which showed higher titres in the immunocompetent over the entire one-year follow-up. In conclusion, in immunocompromised patients the viral load peak was much higher, while the neutralizing antibody response exceeded that detected in the immunocompetent host starting six months after onset of follow-up, often concomitantly with a lack of specific CD4(+) T cells. In this setting, the elevated antibody response occurred in the presence of differentiated follicular helper T cells in the blood, which decreased in number as did antibody titres upon reappearance of HCMV-specific CD4(+) T cells.